معالجة تأريض النقطة الحيادية (النجمية) في نظم الطاقة الكهربائية - محمود شعيب (Latakia University Journal -Engineering Sciences Series, 2019)
تعرض هذه المقالة دراسة تحليلية للشروط المتمثلة بالأمن والسلامة من الخطر الهندسي في بناء الشبكات الكهربائية وعملها, وبوصف الخطر الهندسي محصلة لقيمتين مؤثرتين هما حجم الضرر واحتمالات الضرر, لذلك قمنا بتقليل القيمتين السابقتين من خلال اقتراح خطوات جديدة في بناء الشبكات الكهربائية وعملها. تبين الإحصائيات أن 80% من مجموع الأعطال في الشبكات الكهربائية للتوترات أعلى من (1 kV) أعطال أحادية الطور (قصر لطور مع الأرض). انطلاقا ً من هذا تم في هذه المقالة معالجة الأعطال الأرضية, وذلك من خلال الدراسة التحليلية لعاملين أساسيين تمثل العامل الأول بتحديد القيم المؤثرة على قيمة تيار العطل الأحادي الطور وتمثل العامل الثاني بتحديد القيم المؤثرة على قيمة عامل التأريض. كما تبين الدراسة أن التأثير على القيمتين السابقتين يتم من خلال معالجة تأريض النقطة الحيادية في الشبكات الكهربائية حيث يمكن من خلال تغيير ممانعة التأريض للنقطة الحيادية (ZNE) تغيير قيمة الممانعة الصفرية (Z0) للشبكة دون تغيير الممانعة الموجبة والسالبة (Z0, Z1), ولقد ناقشت تغيرها بين قيمتين حديتين (ZNE=0, ZNE=∞). وتم التعرض لكيفية التعامل مع الأنواع المختلفة لتأريض النقطة الحيادية, بهدف السيطرة على تيار العطل الأرضي والجهود الناشئة عنه وبالتالي التأثيرات والأخطار الناشئة عنها عبر معالجة تأريض النقطة الحيادية. This paper focuses on an analytical study of the safety conditions of engineering hazards during electrical network construction. Since engineering hazard can be a result of two effective values: the hazard volume and its probability, our aim is to reduce the effects of these two values by suggesting new steps for electrical network construction. Statistics show that 80% of the total number of electrical network faults of voltage higher than (1 kV) is singular-phase-fault (earth-phase-shortness). This study analyses earth faults by studying two basic effects: Determining the values affecting the amount of singular-fault-current. Determining the values affecting the earth-parameter amounts. Also, this research shows that the effects of these two parameters emerge from the singular-point-earth-analysis of electrical networks by changing earthing impedance (variation) of the neutral-point (ZNE), and the zero-impedance value (Z0) of the network without varying the positive and negative impedance (Z0, Z1). The critical values (0 = ZNE = ∞) have also been discussed. We have also studied various kinds of neutral point earthing in order to be able to control the current’s earthing fault, the resultant effects, and the hazardous effects produced by neutral point earthing.